1958
DOI: 10.1111/j.1365-2621.1958.tb17556.x
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARATIVE EVALUATION OF METHODS FOR DETERMINING THE BACTERIAL CONTAMINATION OF SURFACESa

Abstract: Numerous investigations have been conducted to fill the need for simple, reliable, bacteriological tests to determine quantitatively the sanitary quality of food contact surfaces. They have resulted in the development of various swabbing (3, 4, 5, 7, l o ) , rinsing (2, l l ) , and agar contact methods (6,8,9,12). Some methods are better suited for examining flat surfaces than for examining food containers, eating utensils, or processing equipment, etc. ; in fact, there is no one method, presently available, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Other cited errors contributing to poor precision include inconsistent spore release from swabs due to variations in vortexing, sonication, or pipetting, and colony counting errors (2,32). It has been suggested that variations of experiments in laboratory settings are minimal compared to those in application due to a variety of different factors (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cited errors contributing to poor precision include inconsistent spore release from swabs due to variations in vortexing, sonication, or pipetting, and colony counting errors (2,32). It has been suggested that variations of experiments in laboratory settings are minimal compared to those in application due to a variety of different factors (2).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid leftover spores on the swab material and to increase spore detection, some previous studies were done with alginate swabs, which dissolve completely in sodium hexametaphosphate. However, due to low efficiency in spore recovery and growth inhibition of, e.g., B. globigii (currently B. atrophaeus), these swabs were considered to be less applicable to spacecraft bioburden control (2,39). In this study, the maximum recovery efficiency of B. atrophaeus spores from surfaces was detected on carbon fiber-reinforced plastic (62.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that a significant proportion of the biological agent that can be sampled from a solid surface remains adhered to the sampling materials despite efforts to wash it off for testing or is lost during the sample processing (1,7,19).…”
mentioning
confidence: 99%
“…Recovery, enumeration, and identification of microorganisms on surfaces have been a focus of scientific inquiry for over a century, with initial applications primarily related to food safety (2), the integrity of the National Aeronautics and Space Administration (NASA) programs (35), and hygiene in domestic (22,50) and clinical (1,6,19) settings. However, the reliability of traditional surface sampling methods came under intense scrutiny in 2001 following the widespread contamination of multiple large building complexes with spores identified as Bacillus anthracis, the causative agent of anthrax.…”
mentioning
confidence: 99%